2004
DOI: 10.1038/sj.onc.1207144
|View full text |Cite
|
Sign up to set email alerts
|

Myostatin inhibits rhabdomyosarcoma cell proliferation through an Rb-independent pathway

Abstract: Rhabdomyosarcoma (RMS) tumors are the most common soft-tissue sarcomas in childhood. In this investigation, we show that myostatin, a skeletal muscle-specific inhibitor of growth and differentiation is expressed and translated in the cultured RMS cell line, RD. The addition of exogenous recombinant myostatin inhibits the proliferation of RD cells cultured in growth media, consistent with the role of myostatin in normal myoblast proliferation inhibition. However, unlike normal myoblasts, upregulation of p21 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 57 publications
3
37
0
4
Order By: Relevance
“…Myostatin has also been implicated in the regulation of satellite cell activation, proliferation, and self-renewal that accompanies the up-regulation of p21 Waf1,Cip1 (11). However, work by Langley et al (12) showed that myostatin treatment inhibited rhabdomyosarcoma cell proliferation through an Rb-independent mechanism. Therefore, the antiproliferative effects of myostatin could be achieved by utilization of multisignal pathways.…”
mentioning
confidence: 92%
“…Myostatin has also been implicated in the regulation of satellite cell activation, proliferation, and self-renewal that accompanies the up-regulation of p21 Waf1,Cip1 (11). However, work by Langley et al (12) showed that myostatin treatment inhibited rhabdomyosarcoma cell proliferation through an Rb-independent mechanism. Therefore, the antiproliferative effects of myostatin could be achieved by utilization of multisignal pathways.…”
mentioning
confidence: 92%
“…Loss of myostatin results in increased muscle growth due to increased SC number and activation [8]. Furthermore, myoblasts derived from myostatinnull SCs show increased proliferation and enhanced differentiation [12,36]. In contrast, increased levels of myostatin have been shown to inhibit myoblast proliferation, arresting cells at the G 1 to S transition, further resulting in reduced differentiation [7].…”
Section: Muscle Atrophy Seen In Smad3-null Muscles Could Be Due To Inmentioning
confidence: 99%
“…Further investigation showed that the myostatin-stimulated cell cycle arrest was probably due to an increased expression of cyclin-dependent kinase (Cdk) inhibitor p21 Waf1,Cip1 and a decreased cyclin E/Cdk2 activity, which further caused the hypophosphorylation of Rb protein (11). It was also reported that myostatin inhibited rhabdomyosarcoma cell proliferation through an Rb-independent pathway (12). MyoD and myogenin were implicated to participate in myostatin-induced differentiation suppression (10).…”
Section: Introductionmentioning
confidence: 99%